THE DEVELOPMENT OF ISLAMIC EDUCATION IN THE MODERN ERA: INTERNALIZING THE IDEAS OF SOEKARNO AND MUHAMMAD SA’ID RAMADHAN AL-BUTHI - Sholehuddin, Moh.; Hosen, Hosen; Mukit, Abdul; Lekdjaa Djelloul Saiah, Nadia; Abdullah Al-Maamari, Abdulwahab (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Islamic education faces numerous challenges and opportunities in the modern era, requiring a balance between tradition and innovation. Purpose: This study examines the development of Islamic education by integrating the ideas of Soekarno and Muhammad Sa’id Ramadhan Al-Buthi. It explores how Soekarno's educational philosophy, which emphasized nationalism, independence, and the fusion of national and Islamic values, contributed to shaping modern Islamic education. In contrast, Al-Buthi advocated for an Islamic education system rooted in tradition while addressing contemporary challenges without compromising its core principles. Method: By analyzing the works of both thinkers, this qualitative study highlights how combining their ideas can help develop an Islamic education system that is both deeply rooted in Islamic values and responsive to modern scientific advancements. Result: The findings suggest that this synthesis could lead to an Islamic education model that is both forward-thinking and spiritually grounded, providing a comprehensive approach to addressing the demands of today's globalized world. Conclusion: In conclusion, integrating Soekarno’s and Al-Buthi’s ideas offers a promising framework for advancing Islamic education, making it relevant to contemporary societal needs while maintaining its spiritual foundations.